Characteristics and Outcomes of NELL1 Membranous Nephropathy in Lipoic Acid Users and Nonusers - Rupali S. Avasare; Samantha Clark; Rebecca I. Spain; Raghav Wusirika; Robert Rope; Susan Gurley; Madison Stanaway; Miroslav Sekulic; Dominick Santoriello; Andrew S. Bomback; Pietro Canetta; Sitalakshmi J. Iyer; et al. (Kidney International Reports)
Introduction: Neural epidermal growth factor like 1 membranous nephropathy (NELL1 MN) is associated with various secondary etiologies. However, previous studies on the frequency of these associations and their impact on outcomes are limited. We report a large multiinstitutional series of patients with NELL1 MN with a focus on secondary associations, pathology findings, and their impact on outcome. Methods: We retrospectively reviewed clinicopathologic features of NELL1 MN from 3 institutions and analyzed clinical and histologic associations with outcome. Results: Of 70 patients, 53% were male with a median age of 66 years; median proteinuria was 5.9 g/d. NELL1 MN was associated with lipoic acid (36%), heavy nonsteroidal antiinflammatory drug (NSAID) use (27%), autoimmune disease (23%), malignancy (10% recent, 23% any), mercury exposure (1%), and 11% had no known secondary association. At median follow-up of 11 months, 72% achieved complete or partial remission. Remission rate was 91% in patients with lipoic acid-associated NELL1 MN and ≥6 months of follow-up. On multivariable analyses, patients with primary NELL1 MN (adjusted odds ratio [OR]: 19.7, P = 0.01) and increasing degree of tubular atrophy and interstitial fibrosis (IFTA) (adjusted OR 1.1, P = 0.01) were less likely to achieve any remission, whereas complete remission (CR) was associated with lipoic acid use (adjusted OR: 10.9, P = 0.04, 95% confidence interval [CI]: 1.2–100) and lesser degrees of IFTA (adjusted OR: 0.79, P = 0.16, 95% CI: 0.66–0.96). Conclusion: Our findings strengthen the association between lipoic acid and NELL1 MN. Furthermore, our findings suggest that discontinuation of lipoic acid without immunosuppression should be considered as the first-line treatment.